Assessment of DNA damage with an adapted independent reaction time approach implemented in Geant4‐DNA for the simulation of diffusion‐controlled reactions between radio‐induced reactive species and a chromatin fiber. Issue 2 (20th December 2020) - Tran, Hoang Ngoc; Ramos‐Méndez, José; Shin, Wook‐Geun; Perrot, Yann; Faddegon, Bruce; Okada, Shogo; Karamitros, Mathieu; Davídková, Marie; Štěpán, Václav; Incerti, Sébastien; Villagrasa, Carmen
Abstract : Purpose: Simulation of indirect damage originating from the attack of free radical species produced by ionizing radiation on biological molecules based on the independent pair approximation is investigated in this work. In addition, a new approach, relying on the independent pair approximation that is at the origin of the independent reaction time (IRT) method, is proposed in the chemical stage of Geant4‐DNA. Methods: This new approach has been designed to respect the current Geant4‐DNA chemistry framework while proposing a variant IRT method. Based on the synchronous algorithm, this implementation allows us to access the information concerning the position of radicals and may make it more convenient for biological damage simulations. Estimates of the evolution of free species as well as biological hits in a segment of DNA chromatin fiber in Geant4‐DNA were compared for the dynamic time step approach of the step‐by‐step (SBS) method, currently used in Geant4‐DNA, and this newly implemented IRT. Results: Results show a gain in computation time of a factor of 30 for high LET particle tracks with a better than 10% agreement on the number of DNA hits between the value obtained with the IRT method as implemented in this work and the SBS method currently available in Geant4‐DNA. Conclusion: Offering in Geant4‐DNA more efficient methods for the chemical step based on the IRT method is a task in progress. For the calculation of biological damage, information on the position of chemical species is a crucial point. This can be achieved using the method presented in this paper.